Permasalahan Pertanahan pada Daerah Berkepadatan Penduduk Rendah - Reza Nur Amrin; Haidar Muttaqy Zaen; Muhammad Prayoga Dwi Nugraha; Prihariyanda Putra; Rifqian Izza Zaini; Yehuda Rainata Sangkay (Sekolah Tinggi Pertanahan Nasional, 2021)
The results of the Population Census 2020 show that there is an uneven distribution of the population in Indonesia. This raises a different typology of land problems between high population and low population density areas. A small population with a large area can cause problems with the amount of land that is not properly managed. This paper aims to examine land problems from one of the conditions in the area, that is an area with a low population density. The research data comes from online and offline sources regarding population and land. Literature study with qualitative descriptive analysis is used in analyzing land problems. Land problems that can occur in areas with low population density, namely: the existence of maximum excess land area and ownership of the number of lands that exceed the provisions, potential problems in implementing transmigration, and low community interest in the land registration program. Alternative solutions that can be offered include increasing public trust in state administrators, namely by improving the quality of pre-land registration socialization, the performance of land registration services, and empowerment for the community after land registration.Keywords: low population density, land problems, maximum excess land Intisari: Hasil dari Sensus Penduduk 2020 menunjukkan bahwa terdapat persebaran penduduk yang tidak merata di wilayah Indonesia. Hal tersebut menimbulkan tipologi permasalahan pertanahan yang berbeda antara wilayah berkepadatan penduduk tinggi dengan berkepadatan penduduk . Penduduk yang sedikit dengan luas wilayah yang besar dapat menimbulkan permasalahan banyaknya tanah yang tidak terurus dengan baik. Tulisan ini bertujuan mengkaji permasalahan pertanahan pada wilayah dengan kepadatan penduduk rendah. Data penelitian berasal dari sumber online dan offline mengenai kependudukan dan pertanahan. Studi literatur dengan analisis deskriptif kualitatif digunakan dalam menganalisis permasalahan pertanahan. Permasalahan pertanahan yang bisa terjadi pada daerah kepadatan penduduk yang rendah, yaitu: adanya tanah kelebihan luas maksimum dan kepemilikan jumlah bidang tanah yang melebihi ketentuan, masalah pelaksanaan transmigrasi, dan minat masyarakat yang rendah pada program pendaftaran tanah. Alternatif solusi yang dapat ditawarkan antara lain adalah meningkatkan kepercayaan masyarakat terhadap penyelenggara negara yakni dengan cara meningkatkan kualitas sosialisasi pra pendaftaran tanah, kinerja pelayanan pendaftaran tanah, pemberdayaan bagi masyarakat pasca pendaftaran tanah.Kata Kunci: kepadatan penduduk rendah, permasalahan pertanahan, tanah kelebihan maksimum